Image Steganography And Cryptography Using Three Level Password Security - Thomas, Jeena; Roy, Jeena M; M, Malu; Vijayan, Vrinda; S, Anoop (International Journal of Computer Sciences and Engineering, 2020)
Cryptography and Steganography are two favourite techniques used by developers for security reasons.Cryptography is the study of information hiding and verification. It includes the protocols,algorithms and strategies to securely and consistently prevent or delay unauthorized access to sensitive information and enable verifiability of every component in a communicate.Steganography is the process of hiding text in an image.we propose an encrypting system which combines techniques of cryptography and steganography with data hiding which is highly useful in secret keeping areas. Image steganography and cryptography using three level security is used for transferring text message from sender to receiver.The main aim of project is to provide the user a secure way that helps the user to send and receive secret messages.There is three level authentication system that validates user for accessing the system only they have input correct one time password.The project involves three levels of authentications for the sender and receiver. In this sender will have to first go through all the three stages of authentication.After going through all the stages the senders text will be encrypted using the cryptography algorithm.These encrypted text will be hidden inside the image.After getting this image he can be send this image and verify OTP to receiver’s mobile number.The receiver also has to through all the stages of authentication and use one time password for verification and decrypt the image and get the message hidden inside the image.